A Comparison of Deceptive and Non-Deceptive Placebo Analgesia: Efficacy and Ethical Consequences. Issue 2 (19th December 2016) - Mundt, Jennifer M.; Roditi, Daniela; Robinson, Michael E.
Abstract: Background: Research has demonstrated the efficacy of analgesic placebos. The manner in which they are usually delivered deceptively raises questions about their impact on recipients. However, there has been little empirical investigation into the potential harms of analgesic placebo. Moreover, the role of deception in determining the magnitude of analgesic placebo response remains poorly understood. Purpose: This study aimed to investigate the consequences of deceptive placebo analgesia in terms of ethical/psychological effects and efficacy. Methods: Healthy adults ( N  = 75) were randomized to a control group, deceptive placebo manipulation, or non-deceptive placebo manipulation. All participants underwent repeated pain testing using a thermal stimulus. Placebo manipulation groups underwent placebo conditioning involving a cream that was described as being either analgesic or inert. State-specific negative mood and attitudes toward research and pain treatment were assessed before and after placebo conditioning. Results: Deceptive and non-deceptive placebo manipulations yielded pain ratings that did not differ significantly from one another but did differ from those of the control group, which experienced a pain sensitization response across trials. Results thus indicated that both deceptive and non-deceptive placebo manipulations prevented pain sensitization. Across groups, the participants reported improved depression, anxiety, frustration, and fear. The use of placebo did not negatively impact participants' attitudes and beliefs about research or pain treatments. The participants tended to rate several parameters related to research participation more positively after participating in our study. Conclusions: Our results indicate that the placebo manipulation groups experienced an anti-sensitization effect. The use of analgesic placebo did not result in any detrimental ethical or psychological effects.